Variables Affecting Financial Performance Of Islamic Commercial Banks With NOM As Mediation - Mail Hilian Batin; Dini Rahmayanti; Heri Kurniawan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2022)
The purpose of this research is to examine the variables that effect financial performance mediated by NOM. The independent variables in this research are NPF, BOPO, FDR, and BASIL and ROA as the dependent variable. The population in this study were 14 Islamic Commercial Banks. 9 Islamic Commercial Banks were used as samples. The data is taken from the quarterly financial statements for the 2019-2020 period. The analytical technique used is Multiple Regression test with path analysis. The BASIL variable has a positive effect on NOM and a negative effect on ROA. The BOPO variable has no effect on NOM and has a positive effect on ROA. The FDR variable has a negative effect on NOM and has a negative effect on ROA. The NOM variable has a positive effect on ROA. The NPF variable has a positive effect on NOM and has no effect on ROA. Then the variable NOM succeeded in mediating the BASIL, BOPO, FDR and NPF variables on ROA. For future research, it is necessary to make observations for a longer time and include risk variables on profitability and choose other sectors besides Islamic Commercial Banks